Mild Cognitive Impairment or Attention-Deficit/Hyperactivity Disorder in Older Adults? A Cross Sectional Study - Mendonca, Felippe; Sudo, Felipe Kenji; Santiago-Bravo, Gustavo; Oliveira, Natalia; Assuncao, Naima; Rodrigues, Fernanda; Soares, Rejane; Calil, Victor; Bernardes, Gabriel; Erthal, Pilar; Drummond, Claudia; Tovar-Moll, Fernanda; et al. (Frontiers in Psychiatry, 2021)
Background: Attention-Deficit/Hyperactivity Disorder (ADHD) is a highly prevalent neurodevelopmental condition, which may be associated with life-enduring cognitive dysfunction. It has been hypothesized that age-related cognitive decline may overlap with preexisting deficits in older ADHD patients, leading to increased problems to manage everyday-life activities. This phenomenon may mimic neurodegenerative disorders, in particular Mild Cognitive Impairment (MCI). This cross-sectional study aims to assess cognitive and behavioral differences between older subjects with ADHD and MCI. Methods: A total of 107 older participants (41 controls; 40 MCI and 26 ADHD; mean age = 67.60 ± 7.50 years; mean schooling = 15.14 ± 2.77 years; 65.4% females) underwent clinical, cognitive, and behavioral assessments by a multidisciplinary team at the Memory Clinic, D'Or Institute for Research and Education, Rio de Janeiro, Brazil. Mean scores in neuropsychological tasks and behavioral scales were compared across groups. Results: Participants with ADHD showed poorer performances than controls in episodic memory and executive function with large effect-sizes. Performances were comparable between MCI and ADHD for all domains. Discussion: MCI and ADHD in older individuals are dissociated clinical entities with overlapping cognitive profiles. Clinicians ought to be aware of these converging phenotypes to avoid misdiagnosis.